EDUKASI GIZI SISWA SDN 30 AIR DINGIN KOTA PADANG MELALUI MEDIA KOMIK DAN BUKU SAKU UNTUK PENCEGAHAN OBESITAS DAN STUNTING - Resmiati Resmiati; Putri Aulia Arza; Muhammad Aldrian; Adinda Tri Maiyusfa; Annisa Fitri; Muhammad Fathu Ridho; Muhammad Agung Satriya (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Stunting and Obesity are major nutritional problems in Indonesia. More than 6 million out of 23 million Indonesian children in 2021 are stunted. Around 18–19% of children aged 5–12 years (elementary school children) in Indonesia are overweight, and 11% are obese. The purpose of this community service is to educate elementary school children so that they have adequate knowledge and attitudes towards nutrition, obesity and stunting, and have the ability to measure nutritional status to prevent stunting and obesity problems. This activity was carried out at SDN 30 Air cold, Koto Tangah District, Padang City. The method used is the lecture method using media and training methods. The media used in this activity are comics and pocket books. While the training conducted was training on measuring nutritional status for elementary school children. The result of this activity is an increase in elementary school children's knowledge of nutrition, obesity, and stunting, from 36% to 100%. In addition, the target group has the skills to properly and correctly measure the nutritional status of themselves and others. They understand when someone is said to be stunted and obese from the results of measuring their nutritional status. These skills reinforce the target group's understanding and knowledge of stunting and obesity. It is hoped that schools continue education through local content subjects and use the pocket books that have been provided and monitor the nutritional status of all students on a regular basis through the UKS (School Health Unit) program.